Numerical Test Study on the Failure Mechanism of Coal-Rock Combined Body under the Coupling Action of Hydraulic and Mechanical - Feng Chen; Jinguo Lv; Yue Yin; Chunpeng Qi (Geofluids)
Coal and rock are often in an environment of hydraulic-mechanical coupling. In order to study the failure mechanism of the coal-rock combined body under the coupling action of hydraulic and mechanical, the RFPA-Flow software was used to analyze the failure mode, strength change law, and acoustic emission change law of the coal-rock combined body with different rock-to-coal height ratios under the combined action of uniaxial load and water pressure. The research results show that the peak strength, residual strength, and stress drop of coal-rock combined body with different rock-to-coal height ratios decrease after water pressure, which reduces the occurrence probability of rock bursts. However, the stress showed a vertical drop phenomenon in the later stage of loading, indicating that the coal-rock combined body still maintains the characteristics of brittle failure after being softened by water, and the roadway may still have rock bursts. The research conclusions can provide a theoretical basis for using water injection measures to prevent rock bursts in deep coal and rock masses.